Correlation between histidine operon expression and guanosine 5'-diphosphate-3'-diphosphate levels during amino acid downshift in stringent and relaxed strains of Salmonella typhimurium. - Shand, R F (1989)
We have analyzed the correlation of attenuator-independent expression of the Salmonella typhimurium histidine operon in vivo with levels of the "alarmone" guanosine 5'-diphosphate 3'-diphosphate. Amino acid downshift caused by serine hydroxamate addition increased his expression in a relA+ strain and decreased his expression in a relA mutant, whereas levels of guanosine 5'-diphosphate-3'-diphosphate varied in parallel with the changes in his expression in the two strains. In several experiments, overall variations in his expression ranged from 20- to 60-fold after downshift. The mild downshift allowed growth of the cultures to continue at near-preshift rates. Serine hydroxamate addition was also used to analyze the effect of amino acid downshift on induced expression of wild-type and mutant lac promoters. There was a 12-fold difference in lac expression when a relA+-relA1 pair was subjected to mild starvation but only a 3-fold difference when the strains carried the lacZpL8UV5 promoter mutation. These results suggest that guanosine 5'-diphosphate-3'-diphosphate stimulates gene expression in vivo at the level of transcription initiation.